COMPARATIVE EVALUATION OF SIMULATED PLAQUE BIOFILM REMOVAL FROM A MODEL ROOT SURFACE FOLLOWING THREE DIFFERENT DEBRIDEMENT METHODS: AN IN-VITRO STUDY (CAHIERS MAGELLANES-NS, 2024)
Aim: The aim of this study was to evaluate and compare the difference in the amount of removal of simulated biofilm from root surface following root surface debridement [RSD] using three different intervention modalities in an in-vitro model assessed by digital subtraction image analysis.Methods and Material: An anatomical model of mesial aspect root of 36 was sprayed with articulation spray to simulate dental biofilm. This model was subjected to RSD using standard gracey’s curette #15-16(Group A), ultrasonic root debridement with HC tip (Group B), and glycine powder air abrasion(Group C).The difference between pre and post debridement mean grey value depicting surface area of simulated biofilm removed from root surfaces assessed for probing depth zones from 0 up-to 3mm(zone 1), more than 3 up-to 6mm(zone 2) and more than 6mm(zone 3).Statistical analysis: The data for all three groups demonstrated normal distribution which was checked using Shapiro-Wilk test.Inter group comparison (>2 groups) was done using one way ANOVA followed by pair wise comparison using post hoc test.Results: Upon inter-group pair wise comparison group A demonstrated the most reduction in post debridement mean grey values as compared to group B and C in all three probing depth zones1,2 and 3 respectively(p-value = 0.00). Inter-group comparison between Group B and Group C demonstrated no significant difference in reduction in post debridement mean grey valuesin probing depth zone 1, 2 and 3. (p-value>0.05)Conclusions: Debridement with curettes is most efficacious in RSD for all probing depths as compared to ultrasonic scaling and air abrasion.